1982
DOI: 10.1007/bf00965529
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis and transport in the regenerating goldfish visual system

Abstract: The nature of the proteins synthesized in the goldfish retina and axonally transported to the tectum during optic nerve regeneration has been examined. Electrophoretic analysis of labeled soluble retinal proteins by fluorography verified our previous observation of a greatly enhanced synthesis of the microtubule subunits. In addition, labeling of a tubulin-like protein in the retinal particulate fraction was also increased during regeneration. Like soluble tubulin, the particulate material had an apparent MW o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 38 publications
6
57
0
Order By: Relevance
“…Particular interest has been placed in identifying proteins that are induced in the ganglion neuronal cell during regeneration in this system (14,(16)(17)(18)(19)(20)(21). Some of these proteins might prove regulatory and essential for the regeneration process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Particular interest has been placed in identifying proteins that are induced in the ganglion neuronal cell during regeneration in this system (14,(16)(17)(18)(19)(20)(21). Some of these proteins might prove regulatory and essential for the regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that both retinal RNA (9)(10)(11)(12) and protein (13)(14)(15) turnover increase following optic nerve axotomy. Specific retinal growthassociated proteins (GAPs) appear to be induced (16)(17)(18)(19)(20)(21), and there is a marked increase in the synthesis of constitutive cytoskeletal components, such as tubulin (14,17). Among the induced proteins, an acidic protein doublet (p68/70; pl 4.8-4.9) was detected by the in vivo labeling of newly synthesized proteins with radioactive precursors (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rapidly axonally transported proteins associated with neuronal growth and regeneration have been identified (Skene and Willard, 1981;Heacock and Agranoff, 1982;Benowitz and Lewis, 1983;Katz et al, 1985). More recently, it has been demonstrated that one of these proteins, designated growth-associated protein 43 (GAP43), is characteristic of growth cones (Meiri et al, 1986).…”
Section: Neuronal Plasticitymentioning
confidence: 99%